2017
DOI: 10.1080/00016489.2017.1398839
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum lactate dehydrogenase as a prognostic indicator for oral cavity squamous cell carcinoma

Abstract: Pretreatment serum LDH is an independent prognostic factor for overall survival in patients with OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The determined AIC value was lower for model 1 than for model 2, and the adjusted R 2 value for model 1 was higher than that for model 2. This suggests that model 1 had a higher predictive accuracy for PB NGAL levels than did model 2 (Table ) . In both models, the only significant independent variable was neutrophil count ( P = 0.000).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The determined AIC value was lower for model 1 than for model 2, and the adjusted R 2 value for model 1 was higher than that for model 2. This suggests that model 1 had a higher predictive accuracy for PB NGAL levels than did model 2 (Table ) . In both models, the only significant independent variable was neutrophil count ( P = 0.000).…”
Section: Resultsmentioning
confidence: 92%
“…When independent variables presented variance influence factor (VIF) values >10, those independent variables were considered to have multicollinearity. The predictive accuracy of the multiple regression models was assessed using Akaike's information criterion (AIC) and adjusted R 2 values . Statistical significance was set at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AIC value was lower for Model 1 than for Model 2, and the adjusted R 2 value for Model 1 was higher than that for Model 2. This suggested that model 1 had higher predictive accuracy for NGAL normalized counts than model 2 (Table 3) [19,20]. However, multiple regression analysis showed multicollinearity between TLR4 (VIF=17.277) and STAT3 (VIF=22.683), two independent variables in model 1 (Table 3).…”
Section: Multiple Regression Analysis Of the Normalized Counts Of Ngal And Those Of Other Cytokine Genesmentioning
confidence: 95%